INSKRIPSI BERHURUF ARAB DI KOMPLEKS MAKAM TROLOYO (KAJIAN TERHADAP GAYA PENULISAN, ARTI DAN MAKSUD INSKRIPSI, SERTA KRONOLOGINYA) - Muhammad Chawari (BRIN, 1997)
From the Troloyo Tomb Complex, it can be seen various aspects of archaeology related to the development of Islam, especially in East Java. More specifically, it is closely related to the existence of the Majapahit Kingdom. From various kinds of research that have been done, both by foreign and national researchers, we knew regarding the chronological data, the location of the tomb complex, decorative styles, and data on inscriptions. They are also known to have historical values, political values, cultural values, and also religious values that underlie them.